Infant death due to nutritional anemia in Brazil between 2008 and 2020: an epidemiological study (Research, Society and Development, 2023)
Anemia is characterized by a low level of hemoglobin in the blood. In children, this pathology is a serious problem, since it is harmful to the development of the child's body and sometimes causes death. Thus, this work aims to describe the epidemiological profile of infant deaths due to nutritional anemia between Brazilian regions in the period 2008 and 2020. Therefore, it is an ecological, cross-sectional, retrospective, descriptive and quantitative study, from secondary data from the Department of Informatics of the Unified Health System, following the variables: region, period, place of occurrence, age group, gender, ethnicity/race, mother's age, education, duration of pregnancy, type of pregnancy, type delivery and birth weight. In which the research identified the Northeast with the highest death rate (53%), followed by the North (27%), Southeast (9.2%), Midwest (5.8%) and South (3.3%), representing a large disparity between regions. The factors that cause such disparity are closely linked to the socioeconomic conditions that individuals find themselves. Thus, it is essential to combat socioeconomic inequalities, promoting equal access to health services to combat infant mortality through early diagnosis. Thus, making infant mortality due to nutritional anemia less incident.